The use of multi-criteria decision analysis in the selection of suppliers using the example of a manufacturing company = Zastosowanie wielokryterialnej analizy decyzyjnej przy wyborze dostawców na przykładzie przedsiębiorstwa produkcyjnego - Danielak, Wiesław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to identify the criteria for selecting suppliers and applying multicriteria decision analysis when selecting suppliers on the example of a manufacturing company. The article is of a theoretical and empirical nature. The theoretical part presents the role of suppliers in the supply chain based on literature studies and indicates various criteria for selecting suppliers. As part of the empirical research, analyzes were carried out on the example of a small manufacturing enterprise. The analytical hierarchical process (AHP) method was used to select and evaluate suppliers.
Keywords: łańcuch dostaw; wielokryterialna analiza decyzyjna; przedsiębiorstwo produkcyjne; supply chain; multi-criteria decision analysis; manufacturing company